When clothing comfort meets aesthetics - Matté, L. L. (2019)
This study examines the results obtained in the first phase of a PhD research on the psychological comfort of clothing. At this initial stage, a variation of the Delphi Method was used to seek opinions from experts about the concept of psychological comfort and which factors would intervene in its perception. The results converge to suggest that aspects related to aesthetics are among the most important attributes to be considered in the process of assessing the psychological dimension of clothing comfort. Therefore, the present paper supports the hypothesis raised by the literary revision, which argues that the aesthetic dimension has great relevance for the comfort of clothing. It also corroborates that the investigations on the psychological comfort of clothing can benefit from considering the importance of aesthetics in the interaction between person-clothing-environment, both in terms of appearance (vision) and of pleasure aroused by clothing and perceived by the totality of the senses.